Case report: Exploring under the tip of the iceberg: A case series of "self-limiting" multisystem inflammatory syndrome in children - Alessandra Meneghel; Giorgia Martini; Marta Balzarin; Nadia Zabadneh; Michele Fastiggi; Francesca Tirelli; Francesco Zulian (Frontiers Media S.A., 2022)
Multisystem inflammatory syndrome in children (MIS-C) is a serious condition triggered by SARS-COV-2 infection, characterized by persistent fever, multiorgan dysfunction, and increased inflammatory markers. It requires hospitalization and prompt treatment, with nearly 60% of the cases needing intensive care and 2% fatality rate. A wide spectrum of clinical characteristics and therapeutic approaches has been reported in MIS-C. We describe a series of four patients with MIS-C, defined according to the current case definitions, with a self-limiting course and no need for immunomodulatory treatment ("self-limiting MIS-C"). Few data about self-limiting MIS-C are available to date and no information on medium- and long-term outcome of this subset of patients has been reported. Although limited in size, our experience provides new insights into the MIS-C syndrome, highlighting an underestimated aspect of the disease that may have significant therapeutic implications.